Causes and trends in modern geopolitical changes - Budanov, Kyrylo; Vereshchak, Vasyl; Kudriavtsev, Volodymyr; Mokliak, Sergii; Rubel, Karina (Edelweiss Applied Science and Technology, 2024)
In today's world, geopolitical transformations are gaining particular importance, creating new challenges and opportunities for countries. The article aims to identify the causes of geopolitical transformations and determine the main directions of their development. The research methodology involves a holistic approach to the economic development of the world economy, the study of the main geopolitical trends, and the assessment of the impact of military conflicts and competition in digital technologies. The study results revealed that the growth of the economic power of the new centres of power causes a redistribution of global economic resources. In turn, military conflicts, such as the war in Ukraine and Israel, significantly affect international relations. The results revealed increased competition in digital technologies, affecting countries' global competitiveness. The study's practical significance lies in determining the strategic directions of the countries' development in the conditions of geopolitical transformation and providing recommendations to reduce the negative consequences of the economic slowdown. The article outlines the role of innovation and technological progress in maintaining economic stability and security. Several recommended measures are provided to increase the stability of national economies and strengthen international cooperation. The prospects for further research are developing political and economic strategies that consider the specifics of modern geopolitical processes.